1998
DOI: 10.1074/jbc.273.11.6183
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Cytoplasmic Protein That Specifically Binds to Nuclear Localization Signal Motifs

Abstract: Active transport of proteins into the nucleus is mediated by interaction between the classical nuclear localization signals (NLSs) of the targeted proteins and the NLS receptor (importin) complex. This nuclear transport system is highly regulated and conserved in eukaryotes and is essential for cell survival. Using a fragment of BRCA1 containing the two NLS motifs as a bait for yeast two-hybrid screening, we have isolated four clones, one of which is importin ␣. Here we characterize one of the other clones ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
109
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 43 publications
(50 reference statements)
3
109
0
1
Order By: Relevance
“…Confocal microscopy showed that Rta and BRAP2 co-localized in the cytoplasm (Fig. 3), which is consistent with the knowledge that BRAP2 is a cytoplasmic protein (Asada et al, 2004;Li et al, 1998).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Confocal microscopy showed that Rta and BRAP2 co-localized in the cytoplasm (Fig. 3), which is consistent with the knowledge that BRAP2 is a cytoplasmic protein (Asada et al, 2004;Li et al, 1998).…”
Section: Discussionsupporting
confidence: 73%
“…As BRAP2 interacts with the NLS in BRCA1 and p21 to retain these two proteins in the cytoplasm (Asada et al, 2004;Li et al, 1998), we investigated whether expression of BRAP2 also retained Rta in the cytoplasm. To accomplish this, 293(maxi-EBV) cells were transfected with pHA-BRAP2 and treated with TPA and sodium butyrate.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the timing or signal for nuclear translocation, p73b protein is translocated into the nucleus, where it exerts transcriptional activity and cell death. Consistent with our proposal, several investigators suggest that one of the inactivation mechanisms of the tumor suppressor involves cytoplasmic sequestration (Moll et al, 1992;Darzynkiewicz et al, 1992;Li et al, 1998). In the case of p53, the tumor-suppressor protein is found in the cytoplasm in tumor tissue from breast cancer, and neuroblastoma Moll et al, 1996).…”
Section: Discussionsupporting
confidence: 67%
“…Considering the interaction between BRAP protein and Breast Cancer 1 protein (BRCA1), 21 there was a possibility that a significant association of CAD with BRAP in the Korean population might be obtained because of a selection bias in the controls, because Korean cancer patients without CAD were included in the control panel in addition to the random healthy individuals. However, there was no significant difference in the minor allele frequencies of the BRAP SNP among patients with stomach cancer (0.189, n¼230), colon cancer (0.143, n¼147), lung cancer (0.201, n¼87) and hepatocellular carcinoma (0.190, n¼71), compared with the random healthy individuals (0.191, n¼178), suggesting that the BRAP SNP was a genetic risk factor for CAD and was not related to the cancer phenotype in the Korean population.…”
Section: Discussionmentioning
confidence: 99%